Introduction (Introduction_IV_XVI) - Shelton, John C. (BrillOnline Reference Works, 2012)
It was probably in December of 1945 that a party of Egyptian sabakh-diggers discovered under the sheltering side of a fallen boulder the sealed jar which when broken open was found to contain the manuscripts that are now known as the Nag Hammadi Library. Reportedly the jar was discovered together with a corpse (though not from an ancient burial) on a bed of something resembling charcoal, but this was not confirmed by excavations on or near the site thirty years later in December 1975. However that may be, one of the party, Mohammed Ali, took the manuscripts back to his home in al-Qasr, the ancient Chenoboskia, some three and a half miles from the place of discovery near the tiny village Hamra Dom. There he deposited them among straw that was to be used as fuel for a clay oven in the courtyard, and some of the material was consequently later burned; but much the greater part was saved and eventually came into possession of the Coptic Museum in Old Cairo, where it is kept today